Association of prevalence of active transport to work and incidence of myocardial infarction: A nationwide ecological study. (29th August 2020) - Munyombwe, Theresa; Lovelace, Robin; Green, Mark; Norman, Paul; Walpole, Sarah; Hall, Marlous; Timmis, Adam; Batin, Phil; Brownlee, Alistair; Brownlee, Jonathan; Oliver, Ged; Gale, Chris P
Abstract: Background: There is a paucity of population-based geospatial data about the association between active transport and myocardial infarction. We investigated the association between active transport to work and incidence of myocardial infarction. Design: This ecological study of 325 local authorities in England included 43, 077, 039 employed individuals aged 25–74 years (UK Census, 2011), and 117, 521 individuals with myocardial infarction (Myocardial Ischaemia National Audit Project, 2011–2013). Methods: Bayesian negative binomial regression models were used to investigate the association of active transport to work and incidence of myocardial infarction adjusting for local levels of deprivation, obesity, smoking, diabetes and physical activity. Results: In 2011, the prevalence of active transportation to work for people in employment in England aged 25–74 years was 11.4% (4, 531, 182 active transporters; 8.6% walking and 2.8% cycling). Active transport in 2011 was associated with a reduced incidence of myocardial infarction in 2012 amongst men cycling to work (incidence rate ratio (95% credible interval) 0.983 (0.967–0.999); and women walking to work (0.983 (0.967–0.999)) after full adjustments. However, the prevalence of active transport for men and women was not significantly associated with the combined incidence of myocardial infarction between 2011–2013 after adjusting for physical activity, smoking and diabetes. Conclusions: In England, the prevalence of active transportation was associated with a reduced incidence of myocardial infarction for women walking and men cycling to work in corresponding local geographic areas. The overall association of active transport with myocardial infarction was, however, explained by local area levels of smoking, diabetes and physical activity.